O Sertão de Papel de Natércia Campos: Memória das Trindades - Timbó, Margarida Pontes (2011)
In this study we seek to stop on the process of artistic creation of the writer from Ceará Natércia Campos, basing especially in the reading and analysis of literary manuscripts, notebooks and researches relating to the novel The House (1999). These documents are in Arquivo do Escritor Cearense- AEC, located in the Human Science Library of the Federal University of Ceará. Being conscious that the writer has elaborated a study project before writing her only novel, we sought to investigate her researches and observe how they were incorporated into her work. The methodology used is bibliographic-theoretical and occurred in three directions: first, starting from the reading and analysis of the writer‟s manuscripts, then from the researches made by her in order to establish the comparison with the final text of the novel. Finally, we sought to build the Natércia‟s profile as a reader, following within the novel some features of the readings that she made. We are based on authors like Cecília Almeida Salles (2000), (2004), Philippe Willemart (1993), Ítalo Gurgel (1997), Leyla Perrone-Moisés (1990), Elizabeth Sampaio Alencar Lima (2009), Maria Zilda Ferreira Cury (1993) among others. Within the scope of the culture, we leaned especially on Câmara Cascudo (2000), (2002a) (2002b), a researcher with a strong presence in Natércia Campos‟ collection